Toxicity of organic selenium (Selemax) and its effects on haematological and biochemical parameters and histopathological changes of common carp (Cyprinus carpio L., 1758). (1st October 2016) - Yeganeh, Sakineh; Adel, Milad; Ahmadvand, Sharareh; Ahmadvand, Sheyda; Velisek, Josef
Abstract: The aim of this study was to assess the effect of organic selenium (Selemax) on Common carp ( Cyprinus carpio ). The effect was determined on basis of acute toxicity, haematological, biochemical profile and histopathology. A static toxicity test was performed for the determination of 96 h median lethal concentration. The 96hLC50 value of Selemax was 0.54 mg/L. For investigation of chronic toxicity, the experimental group exposed to Selemax in concentration 0.054 mg/L (10% 96hLC50) during 28 days showed significant changes in haematological and biochemical profile and caused histopathological changes in liver, and kidney. According to those data, it was possible to classify organic selenium as highly toxic for carp. The alterations of these parameters can be used as suitable biomarkers in monitoring of organic selenium in the aquatic environment.